Health behaviors of late adolescents in China: Scale development and preliminary validation - Qiu, Qian; Dai, Shengting; Yan, Jingfei (Frontiers in Psychology, 2022)
Health behaviors influence health and well-being, improve quality of life, and provide economic benefits. It is important to take advantage of health-related opportunities during adolescence. Staying healthy during adolescence also promotes the future well-being of individuals and that of the next generation. We aimed to develop a reliable and valid scale based on the General Senior High School Physical Education and Health Curriculum Standards (2017 edition) to evaluate Chinese late adolescents’ health behavior. The scale was to help physical education teachers measure the health behavior level of senior high school students, improve physical education and health teaching, and promote Chinese adolescent health. Participants were recruited by convenience sampling from September to October 2019. For the first survey, we recruited 526 senior high school students (318 boys, 208 girls; Mage = 16.5), and the data were subjected to item analysis and exploratory factor analysis. For the second survey, we recruited 542 senior high school students (249 boys, 293 girls; Mage = 15.5), and the data were subjected to confirmatory factor analysis and internal consistency reliability analysis. After exploratory factor analysis, we extracted four factors with 23 items: exercise awareness and habits (five items), mastering and applying healthy behavior knowledge (ten items), emotional regulation (four items), and environment adaptation (four items). The Cronbach’s alpha values for these factors ranged from 0.863 to 0.937. After confirmatory factor analysis, we achieved a satisfactory goodness-of-fit model (CMIN/DF = 2.92, RMR = 0.03, GFI = 0.93, CFI = 0.91, TLI = 0.92, RMSEA = 0.06). Internal consistency, test-retest reliability, and construct validity were all satisfactory. These results suggest that the Chinese version of the Health Behavior Scale is a reliable and valid instrument for assessing the health behavior of senior high school students. The findings have important implications for increasing adolescents’ health literacy, promoting adolescents’ health, and enhancing the well-being of late adolescents.